2021
DOI: 10.1097/j.jcrs.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and clear corneal incision cataract surgery

Abstract: Clear corneal incision cataract surgery with pupillary expansion devices and local anesthetic injections can be safely performed in patients with thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We read with great interest the study by Reilly et al, in which the authors described complications and outcomes of clear corneal incision cataract surgery in a large cohort of patients with thrombocytopenia. 1 In their retrospective review, the authors found only 2 cases (1%) of intraoperative iris hemorrhage of 196 eyes from 150 thrombocytopenic patients. This study provides evidence that preoperative testing for thrombocytopenia before cataract surgery is unlikely to benefit patients.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We read with great interest the study by Reilly et al, in which the authors described complications and outcomes of clear corneal incision cataract surgery in a large cohort of patients with thrombocytopenia. 1 In their retrospective review, the authors found only 2 cases (1%) of intraoperative iris hemorrhage of 196 eyes from 150 thrombocytopenic patients. This study provides evidence that preoperative testing for thrombocytopenia before cataract surgery is unlikely to benefit patients.…”
mentioning
confidence: 98%
“…Perioperative preparation for thrombocytopenic or anticoagulated patients is challenging for surgeons, with the obvious risk being intraoperative bleeding. 1–5 Recently, we have retrospectively studied the hematologic and ocular factors that may affect intraocular hemorrhage risk during clear cornea cataract surgery in anticoagulated patients. In 299 patients taking anticoagulants for at least 6 months, 16 of 229 eyes (6.9%) experienced intraoperative hemorrhage (ie, iris bleeding) (Table 1).…”
mentioning
confidence: 99%